2019
DOI: 10.1002/hyp.13403
|View full text |Cite
|
Sign up to set email alerts
|

Flow field downstream of individual aquatic plants—Experiments in a natural river with Potamogeton crispus L. and Myriophyllum spicatum L.

Abstract: Flow disturbances generated by individual patches of submerged, flexible aquatic vegetation were investigated for two naturally growing macrophyte species, Potamogeton crispus L. and Myriophyllum spicatum L., in a sandy lowland river. Through acoustic Doppler velocimetry, 24 vertical profiles of the 3D velocity field were recorded downstream of each of the patches. The morphological features and biomechanical properties of the plants were also evaluated. The experiments showed the relationship between biomecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…In the Halswell river it is likely that fine sediment was preferentially transported down flow paths between the dense vegetation, then laterally transported and/or diffused into the dense stands of vegetation where accumulation was observed. This is a similar configuration of vegetation, flow and sedimentation to Cotton et al (2006) and Box et al (2019), rather than the isolated vegetation patches of Sand‐Jensen (1998), Biggs et al (2019) and Przyborowski et al (2019). At the study sites of Cotton et al (2006) an accumulation of 6–16 cm of fine sediment was reported within dense macrophyte stands.…”
Section: Discussionsupporting
confidence: 70%
“…In the Halswell river it is likely that fine sediment was preferentially transported down flow paths between the dense vegetation, then laterally transported and/or diffused into the dense stands of vegetation where accumulation was observed. This is a similar configuration of vegetation, flow and sedimentation to Cotton et al (2006) and Box et al (2019), rather than the isolated vegetation patches of Sand‐Jensen (1998), Biggs et al (2019) and Przyborowski et al (2019). At the study sites of Cotton et al (2006) an accumulation of 6–16 cm of fine sediment was reported within dense macrophyte stands.…”
Section: Discussionsupporting
confidence: 70%
“…In a similar way as by Przyborowski et al [61], results obtained in this study may be referred to hydromorphological changes, in the analyzed case connected with transport and sedimentation of fine organic particles. The presence of plants has a considerable effect on the above-mentioned processes.…”
Section: Discussionsupporting
confidence: 69%
“…The growth and community dynamics of submerged macrophytes are influenced by both biotic and abiotic factors, such as light availability, water temperature, nutrient concentrations in both the water and the sediments, and water flow [7,39,40]. The life history-related parameters of aquatic plants will change with the changing circumstances to avoid or resist in order to reduce the potentially negative effects from the adverse environmental conditions [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%